2021
DOI: 10.1101/2021.11.19.21266605
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myocarditis and Pericarditis following COVID-19 Vaccination: Rapid Systematic Review of Incidence, Risk Factors, and Clinical Course

Abstract: Objectives: Myocarditis and pericarditis are adverse events of special interest after vaccination with mRNA vaccines. This rapid systematic review examined incidence rates of myocarditis and pericarditis after COVID-19 vaccination, and the presentation and clinical course of cases. Design: Rapid systematic review Data sources: Medline, Embase and the Cochrane Library were searched from October 2020 to October 6, 2021; reference lists and grey literature (to Oct 21, 2021). Review methods: Randomized controlled… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 44 publications
4
11
0
Order By: Relevance
“…The most common symptoms are chest pain, followed by myalgia/ body aches and fever. These findings matched with Pillay et al (2021) [15], who reported in a systematic review observation that the majority of myocarditis cases had a short symptoms onset of 2 to 4 days after a second dose, and the majority presented with chest pain. These findings matched with Oster et al (2022) [12], who mentioned myocarditis was diagnosed within days of vaccination.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most common symptoms are chest pain, followed by myalgia/ body aches and fever. These findings matched with Pillay et al (2021) [15], who reported in a systematic review observation that the majority of myocarditis cases had a short symptoms onset of 2 to 4 days after a second dose, and the majority presented with chest pain. These findings matched with Oster et al (2022) [12], who mentioned myocarditis was diagnosed within days of vaccination.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, Patone et al (2022) [14] mentioned that the incidence of myocarditis was among England males younger than 40 years old. Similarly, a systematic review study found that the Incidence of myocarditis following mRNA vaccines is low but probably highest in males aged 12-29 years old [15].…”
Section: Discussionmentioning
confidence: 99%
“…(2022) [ 14 ] mentioned that the incidence of myocarditis was among England males younger than 40 years old. Similarly, a systematic review study found that the Incidence of myocarditis following mRNA vaccines is low but probably highest in males aged 12–29 years old [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Forty-six studies were included in this update ( Figure 1 ). Findings from 12 studies from the original review 15 were carried forward (Q1=5 2529 , Q2=2 29 30 , Q3b. 2528 3136 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our original reviews (literature search October 6, 2021) on incidence rates, risk factors, and case presentation and short-term outcomes of myo- and/or pericarditis after COVID-19 vaccination across all vaccines, ages and sexes indicated that incident rates were little-to-none after non-mRNA vaccines and in adults 40 years and older, that rates after mRNA vaccination varied by sex, age, and dose, and that the case characteristics and clinical course of myocarditis and pericarditis differ. 15 There were no data on children aged <12 years or for people after receiving a third dose. For our review update reported herein, we refined the questions to focus on gaps and stakeholder/decision-maker priorities, specifically, mRNA vaccines, priority age and risk groups, and cases after a third vaccine dose.…”
Section: Introductionmentioning
confidence: 99%